A psychometric analysis of the Japanese version of the clinically useful depression outcome scale supplemented with questions for the DSM‐5 anxious distress specifier (CUDOS‐A) - Yumi Aoki; Yoshikazu Takaesu; Yasuyuki Matsumoto; Hitoshi Sakurai; Takashi Tsuboi; Isa Okajima; Hisateru Tachimori; Yoko Komada; Koichiro Watanabe; Mark Zimmerman (Wiley, 2024)
Abstract Aim The aim of the study was to identify the clinical significance of anxiety in those with depression, the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM‐5) defined criteria for an anxious distress specifier for major depressive disorder (MDD). The Clinically Useful Depression Outcome Scale (CUDOS) supplemented with questions for the DSM‐5 anxious distress specifier (CUDOS‐A) is a self‐report instrument to assess the clinical significance of anxiety in addition to assess symptoms and the severity of depression. This study aimed to evaluate the psychometric properties of the Japanese version of the CUDOS‐A. Methods An observational, prospective study was conducted with 131 MDD outpatients and 200 healthy controls. The Japanese version of the CUDOS‐A, along with other measures, was administered to assess depressive symptoms, anxiety, social function, and biological rhythm. Reliability and validity analyses were performed, including internal consistency, test-retest reliability, convergent validity, and contrasted‐groups validity. Results The Japanese version of the CUDOS‐A demonstrated excellent internal consistency (Cronbach's alpha = 0.96) and test-retest reliability (ICC = 0.78). Significant positive correlations were found between the CUDOS‐A and measures of depression, anxiety, social function, and biological rhythm (all, p < 0.001), supporting its convergent validity. The CUDOS‐A effectively differentiated between patients with MDD and healthy controls (p < 0.001), indicating good contrasted‐groups validity. Conclusions The Japanese version of the CUDOS‐A is a useful measure for research and for clinical practice, enabling the efficient assessment of anxious distress in individuals with depression.